Formation of B2 phase and its stability in equiatomic Al-Cu-Fe-Ni-Ti high entropy alloy - Yadav Y.K.; Shaz M.A.; Mukhopadhyay N.K.; Yadav T.P. (My University, 2025)
In the present investigation, we synthesized a single-phase high-entropy alloy in Al-Cu-Fe-Ni-Ti system by melting of the individual metals using a radiofrequency induction furnace under an argon environment. The as-synthesized alloy showed the formation of a B2-type ordered phase with a lattice parameter of 0.289 nm. The mechanical stability of this single phase high-entropy alloy was investigated under high-energy ball milling. The milling was performed at a speed of 400 rpm for 10, 20, and 40 h under a hexane medium with a ball-to-powder ratio of 40:1. The formation of nano crystallites (∼ 10 nm sizes) body centered cubic (BCC) phase (disordered B2) has been observed after 40 h of ball milling, which has been confirmed by X-ray diffraction and transmission electron microscopic investigation. The equiatomic Al-Cu-Fe-Ni-Ti high entropy alloy structure is observed to be quite stable during mechanical milling up to 40 h; only grain refinements and lattice strain accumulation were observed with milling time. © 2024 The Authors